The panel of syntaxin 1 and insulinoma‐associated protein 1 outperforms classic neuroendocrine markers in pulmonary neuroendocrine neoplasms. Issue 4 (28th January 2021) - Zombori, Tamás; Turkevi‐Nagy, Sándor; Sejben, Anita; Juhász‐Nagy, Gréta; Cserni, Gábor; Furák, József; Tiszlavicz, László; Krenács, László; Kővári, Bence
Abstract : Syntaxin‐1 (STX1) is a recently described highly sensitive and specific neuroendocrine marker. We evaluated the applicability of STX1 as an immunohistochemical marker in pulmonary neuroendocrine neoplasms (NENs). We compared STX1 with established neuroendocrine markers, including insulinoma‐associated protein 1 (INSM1). Typical carcinoids (n = 33), atypical carcinoids (n = 7), small cell lung carcinomas ([SCLCs] n = 30), and large cell neuroendocrine lung carcinomas (n = 17) were immunostained using tissue microarray for STX1, chromogranin A, synaptophysin, CD56, and INSM1. Eighty‐four of eighty‐seven (96.5%) NENs showed STX1 positivity. Carcinoids and LCNECs typically presented a combined strong membranous and weak cytoplasmic staining pattern; cytoplasmic expression was predominately observed in SCLCs. The sensitivity of STX1 was 90% in SCLCs and 100% in typical carcinoids, atypical carcinoids, and large cell neuroendocrine lung carcinomas. The overall sensitivity of STX1 in pulmonary NENs was 96.6%, and the sensitivity of the other markers was as follows: chromogranin A (85.2%), synaptophysin (85.2%), CD56 (92.9%), and INSM1 (97.7%). STX1 was found to be an excellent neuroendocrine marker of pulmonary NENs, with sensitivity and specificity surpassing that of classic markers. We propose a panel of STX1 and INSM1 for the routine immunohistochemical workup of pulmonary NENs.